Pilot study on the distribution of caseous lymphadenitis in Korean native goats and the relationship between sex and age in disease occurrence - Aftabuzzaman, Md.; Pioquinto, Jaylord M.; Espiritu, Hector; Valete, Edeneil Jerome; Kim, Seon-Ho; Jin, Su-Jeong; Jung, Myunghwan; Lee, Sang-Suk; Cho, Yong-Il (Frontiers in Veterinary Science, 2023)
Caseous lymphadenitis (CLA) caused by Corynebacterium pseudotuberculosis is a chronic disease that affects goats. The Korean native goat (KNG) is the most popular goat breed raised in Korea. In this study, the distribution of CLA in the KNG population and the relevance of sex and age in disease development were determined. From March 2020 to February 2021, 1,177 KNGs from 110 farms were assessed. The distribution of CLA in animals was determined by a veterinary inspector who performed gross examinations of goat carcasses and confirmed diagnoses via polymerase chain reaction and bacteriological examination. The CLA detection rate in the KNG population was 19.80%, and more than half of the farms were affected by the disease (56.36%). A statistically significant difference was observed among the sex groups, with castrated males (13.98%) having the lowest detection rate, followed by intact males (22.48%) and females (24.09%), suggesting that castration has a positive effect on reducing the risk of CLA (p<0.05). In terms of age groups, an increased detection rate of 28.16% was observed in the late adult (>2 years) group. Phylogenetic analysis indicated that the RNA polymerase beta subunit-encoding gene can effectively differentiate biovar ovis from biovar equi and can be used for further epidemiological studies of C. pseudotuberculosis. This is the first nationwide surveillance study of CLA distribution to confirm the continuous occurrence of CLA in Korean goat farms. Future studies should include risk factor analyses of CLA based on herd levels to prevent and control this disease in Korea.